Simplified multiresidue method for the determination of organophosphorus insecticides in olive oil - Cabras, P.; Angioni, A.; Melis, M.; Minelli, E. V.; Pirisi, F. M. (Elsevier B.V., 1997)
A simple and rapid method for the determination of 13 organophosphorus insecticides and their metabolites in olive oil by GC is described. The pesticide was extracted from oil with acetonitrile and no cleanup was needed. GC-nitrogen-phosphorus detection response factors of pesticides were affected by solvents and coextractive substances. Pesticides in hexane showed on average higher response factors. Standards were prepared in the residue-free oil extract solubilized in hexane to handle effects of matrix and solvent. The low amount of coextractive substances does not decrease the column efficiency, even after a few hundred analyses. Recovery at three fortification levels (ca. 0.1, 1.0 and 3.0 mg/kg) ranged from 74 to 118%, With coefficients of variation ranging from 1 to 16.
Keywords: olive oil; environmental analysis; food analysis; organophosphorus compounds; pesticides